FORM OF ERROR USE OF THE WORD IN SEMANTIC STUDY ON BANNERS IN TANAH GARAM VILLAGE LUBUK SIKARAH DISTRICT SOLOK CITY - Elan - Halid (Jurnal Ilmu Pendidikan Ahlussunnah, 2022)
Language errors are when a person uses a language differently from how that language is supposed to be used. The word "semantics," which has its origins in the Greek language, means "to signify or to interpret." This study was conducted to find out various typographical errors on banners around Tanah Garam village. This research aims to identify many types of errors on banners including ambiguity, redundancy, and meaning ambiguity. The type of study was qualitative research and employed a descriptive approach. While the data source for this study was banners, then the data were presented in the form of words and sentences. Data collection techniques in this study included observation in Tanah Garam Village, taking photos on banners in Tanah Garam Village, and documenting the overall photos. The following data analysis techniques were used in this study: (a) reading or re-observing the banner photos, (b) providing coding by writing the text on the banner and then italicizing the ambiguous word use portion, (c) analyzing the word use research data that was collected, and (d) re-examining the data that was collected regarding the use of words on banners. According to the results of the study, the banner featured a number of flaws, including (1) redundancy of 5 data, (2) ambiguity of 5 data, and (3) ambiguity of meaning for up to 8 data. The ambiguity of meaning is the most prevalent type of error.